Noise levels and noise perception from small and micro wind turbines - Taylor, Jennifer; Eastwick, Carol; Lawrence, Claire; Wilson, Robin (Elsevier, 2013)
Noise concerns frequently pose a barrier to widespread implementation of wind turbines and while the perception of noise from large turbines has been investigated, there is a relative gap in the research for small and micro wind turbines. This paper presents findings from interdisciplinary research linking noise measurements from small wind installations with an investigation into the effect of individual personality traits and noise perception. A survey distributed to households living close to one of 12 micro or small turbine sites, coupled with environmental noise measurements was analysed. The survey showed that the most commonly perceived noises are ‘swooshing’ and ‘humming’, the presence of which may be inferred from the measured frequency spectra. Exploration of survey results showed individuals with a more negative attitude to wind turbines perceive more noise from a turbine located close to their dwelling and those perceiving more noise report increased levels of general symptoms. Individuals' personality also affected attitudes to wind turbines, noise perception from small and micro turbines and symptom reporting.